Bioikon: Alien - Houe, Ulf (Tidsskrift for Medier, Erkendelse og Formidling, 2013)
This essay discusses the Alien movies, their development from older forms, and their impact on modern, popular cinema. Rather than tracing these influences in detail, it develops a number of concepts useful in such a narrative, especially that of a ‘bioiconography’ dependent on a post-Darwinian paradigm. It shows how such a perspective can be applied to an analysis of the ’biosafari’, that is, the opportunity for the audience to participate in an expedition into an environment that is otherwise too dangerous to be seen – and where the threat is biological rather than simply animal. Dette essay handler om Alien-filmene, deres udvikling fra tidligere former og deres indflydelse på moderne underholdningsfilm. I stedet for at fortælle denne historie i detaljer udvikler det en række koncepter der er brugbare til en sådan fortælling. Centralt står konceptet om en ’bioikonografi’ knyttet til det postdarwinistiske paradigme. Det demonstrerer hvorledes et sådant perspektiv kan bruges til en analyse af ”biosafarien,” altså en mulighed for publikum for at deltage i en rejse ind i et territorium der ellers ville være for farligt at opleve – og hvor truslen er biologisk, snarere end blot dyrisk.